Critical path - Fuller, R. Buckminster (Richard Buckminster) 1895-1983 (St. Martin's Press, 1981)
A noted designer and thinker examines our crucial political, economic, ethical, and environmental dilemmas to show how we arrived at the present crisis stage and how humanity can correct its unprecedented threats to Spaceship Earth.